Analisis Pengelolaan Valuta Asing Serta Pasar Valuta Asing Di Indonesia - Nurul Deswita Maharani; Hendra Ibrahim (STIKes Ibnu Sina Ajibarang, 2024)
Muamala Fikh's research requires justification for currency transactions, because buying and selling foreign currency is closely related and cannot be separated from the functioning of the world economy. Foreign currency refers to foreign currencies such as US dollars, pounds sterling and ringgit. An efficient foreign exchange market means exchange rates will change in the future. Unpredictable. The marketing activities of international companies are often organized as separate and independent departments within the company.